Factors Influencing Technological Capability Building in the Nigerian Solar Energy Industry - Adepoju, Adeyemi (Archives of Business Research, 2020)
Technological capability study has continued to gain ground as recognisable progress is being made in the resource-based view (RBV) theory. As a matter of fact, it has become more relevant in the context of a developing nation, such as Nigeria, as a means to create economic development. Using the Panda and Ramanathan methodology for measuring technological capability (TC) in the electric sector, this paper adopted the indicators from the paper to investigate the effects of factors affecting TC on the Nigerian solar energy firms’ TCs. The results of seemingly unrelated regressions showed that both internal and external factors significantly affect technological capability in the solar energy industry in different directions, but similar directions to organizational capability of the solar energy firms’ in Nigeria.